Analysis of Quality Improvement in Learning through Strengthening Visionary Leadership and Teacher Creativity - Muhammad, Nurlaila; Hardhienata, Soewarto; Setyaningsih, Sri (Peneliti.net, 2023)
The aim of this research is to analyze the improvement of learning quality through strengthening visionary leadership and teacher creativity. This study employs a quantitative survey method, with a sample of 219 respondents. Data collection is conducted using a validated and reliable questionnaire. Data analysis techniques include descriptive and inferential analyses using t-tests and coefficient of determination tests. The results indicate that: (1) there is a direct influence of visionary leadership on the quality of learning, falling into the strong category; (2) there is a direct influence of teacher creativity on the quality of learning, also categorized as strong. The conclusion drawn from this study is that the quality of learning can be enhanced through strengthening visionary leadership and teacher creativity.